Educação do campo ou apenas uma mudança de nomenclatura? Um estudo de caso em Santo Antônio do Sudoeste – PR - Nicola, Eduarda (2017)
This research aims understand the ways found for the effective construction of/in the rural education of public school in state of Parana, specifically in Marques do Herval State Rural School, in Santo Antonio do Sudoeste city. The official documents that command the Rural Education in Parana state have the objective of contribute to the management and pedagogical practices in schools located in rural areas. Thus, to accomplish with initial objectives, made the bibliographic review focused in understanding the trajectory in the Rural Education in the brazilian public policies area with the aim of contextualizing the established relationships between the struggle for a Rural Education and related orientations with Operational Guidelines, the State Curricular Guidelines for Rural Education and CEE/CEB N° 1011/10 document. Then, stand out the particularities found in the Political Pedagogical Project and collect dates during the interviews with the managers of the involved schools. Finally, show the projects realized by school that go beyond that is established in the Pedagogical Political Project.